2019
DOI: 10.1042/bsr20190024
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic polymorphisms and osteonecrosis in steroid treatment populations: a detailed stratified and dose-response meta-analysis

Abstract: Steroid treatment has become recognized as an important risk factor for avascular osteonecrosis of the femoral head. However, not all patients who receive long-term, high-dose steroids develop osteonecrosis, indicating that there are individual differences in occurrence. We explored the relationship between polymorphisms and steroid-induced osteonecrosis of the femoral head (SONFH) incidence with variables. We used a multilevel mixed-effects logistic regression model, which is an expansion of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Because of the different types of steroids and units of measurement used in the included studies, it was necessary to convert the different types of steroids into an equivalent dose of hydrocortisone. The conversion standard was hydrocortisone 20 mg = methylprednisolone 4 mg = dexamethasone 0.75 mg. [ 16 ] For pediatric medications, the conversion between body weight (BW) and body surface area (BSA) was as follows: in children with a BW less than 30 kg, BSA(m 2 ) = 0.035 × BW(kg) + 0.1; in children with a BW more than 30 kg, the BSA on a 1.15 m 2 basis increased by 0.1 m 2 per 5 kg increase from a 30 kg BW basis. The primary outcome in our analysis was mortality at the last follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the different types of steroids and units of measurement used in the included studies, it was necessary to convert the different types of steroids into an equivalent dose of hydrocortisone. The conversion standard was hydrocortisone 20 mg = methylprednisolone 4 mg = dexamethasone 0.75 mg. [ 16 ] For pediatric medications, the conversion between body weight (BW) and body surface area (BSA) was as follows: in children with a BW less than 30 kg, BSA(m 2 ) = 0.035 × BW(kg) + 0.1; in children with a BW more than 30 kg, the BSA on a 1.15 m 2 basis increased by 0.1 m 2 per 5 kg increase from a 30 kg BW basis. The primary outcome in our analysis was mortality at the last follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Osteonecrosis of the hip is another side effect of corticosteroids in SOT patients[ 95 ]. Although some studies showed that the cumulative dose of methylprednisolone/prednisolone after kidney transplantation has been a risk factor for avascular osteonecrosis[ 96 , 97 ], a meta-analysis found little correlation between cumulative doses and duration of administration of methylprednisolone/prednisolone and avascular osteonecrosis of the femoral head[ 98 ].…”
Section: Side Effectsmentioning
confidence: 99%